Altered functional connectivity of the primary motor cortex in tremor dominant and postural instability gait difficulty subtypes of early drug-naive Parkinson’s disease patients - Wang, Qi; Yu, Miao; Yan, Lei; Xu, Jianxia; Wang, Yajie; Zhou, Gaiyan; Liu, Weiguo (Frontiers in Neurology, 2023)
Background: The primary motor cortex (M1) is an important hub in the motor circuitry of Parkinson's disease (PD), but the subregions' function and their correlation to Tremor dominant (TD) and postural instability and gait disturbance (PIGD) with PD remain unclear. Our aim was to determine whether the functional connectivity (FC) of the M1 subregions varied between the PD and PIGD subtypes. Methods: We recruited 28 TD patients, 49 PIGD patients and 42 healthy controls (HCs). M1 was divided into 12 regions of interest using the Human Brainnetome Atlas template to compare FC among these groups. Results: Compared with HCs, TD and PIGD patients exhibited increased FC between the left upper limb region (A4UL) and the right cerebellum_6 (CRBL_6)/right caudate nucleus (CAU)/left putamen (PUT), between the right A4UL and the bilateral CRBL_4_5/left PUT/right CAU/left supra marginal gyrus/bilateral middle frontal gyrus (MFG), as well as decreased connectivity between the left A4UL and the left postcentral gurus and the bilateral cuneus, between the right A4UL and the right inferior occipital gyrus; TD patients showed increased FC between the right caudal dorsolateral area 6 (A6CDL) and the left anterior cingulate and paracingulate gyri (ACG)/right MFG, between the left A4UL and the right middle frontal gyrus, orbital part (ORBmid)/bilateral inferior frontal gyrus, orbital part, between the right A4UL and the left ORBmid/right insula (INS); PIGD patients displayed decreased connectivity between the right A4UL and the right INS. Compared with PIGD patients, TD patients exhibited increased connectivity between the right A6CDL and the left ACG/right MFG, and between the right A4UL and the left ACG/left ORBmid/right INS /right MFG. Furthermore, in TD and PIGD groups, the FC strength between the right A6CDL and right MFG was negatively correlated with PIGD scores, while the FC strength between the right A4UL and left ORBmid/right INS was positively correlated with TD scores and tremor scores. Conclusions: Our results demonstrated that early TD and PIGD patients share some common injury and compensatory mechanisms. TD patients occupied more resources in the MFG, ORBmid, INS, and ACG, which can be used as biomarkers to distinguish them from PIGD patients.